2011
DOI: 10.3390/molecules16031956
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Visnagen and Khellin Furochromone Pyrimidine Derivatives and Their Anti-Inflammatory and Analgesic Activity

Abstract: 6-[(4-Methoxy/4,9-dimethoxy)-7-methylfurochromen-5-ylideneamino]-2-thioxo-2,3-dihydropyrimidin-4-ones 1a,b were prepared by reaction of 6-amino-2-thiouracil with visnagen or khellin, respectively. Reaction of 1a,b with methyl iodide afforded furochromenylideneaminomethylsulfanylpyrimidin-4-ones 2a,b. Compounds 2a,b were reacted with secondary aliphatic amines to give the corresponding furochromen-ylideneamino-2-substituted pyrimidin-4-ones 3a-d. Reaction of 3a-d with phosphorus oxychloride yielded 6-chlorofuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 18 publications
0
67
0
Order By: Relevance
“…Condensation of (11b) with acetylacetone, ethylacetoacetate and malononitrile in Zn/AcOH afforded the tetrahydropyrimidinethione derivatives (12)(13)(14), whereas the bis-acetyl derivative (15) was achieved when acetic anhydride was used (Scheme 2), according to the plausible mechanism in (Scheme 3). The 1 H NMR spectrums of (14) exhibited two triplet signals at d 1.20, 4.13 ppm for four protons in pyrimidine ring, a singlet signal 4.70 ppm for four protons of (CH 2 Moreover, the reaction of (11b) with chloroacetyl chloride in ethanol and in the presence of potassium hydroxide gave the corresponding 5-chloro-3-(4-chlorobenzyl)-6-(4-chloro-phenyl)-2-thioxo-tetrahydro-pyrimidi n-4-one (16).…”
Section: Results and Discussion Chemistrymentioning
confidence: 99%
“…Condensation of (11b) with acetylacetone, ethylacetoacetate and malononitrile in Zn/AcOH afforded the tetrahydropyrimidinethione derivatives (12)(13)(14), whereas the bis-acetyl derivative (15) was achieved when acetic anhydride was used (Scheme 2), according to the plausible mechanism in (Scheme 3). The 1 H NMR spectrums of (14) exhibited two triplet signals at d 1.20, 4.13 ppm for four protons in pyrimidine ring, a singlet signal 4.70 ppm for four protons of (CH 2 Moreover, the reaction of (11b) with chloroacetyl chloride in ethanol and in the presence of potassium hydroxide gave the corresponding 5-chloro-3-(4-chlorobenzyl)-6-(4-chloro-phenyl)-2-thioxo-tetrahydro-pyrimidi n-4-one (16).…”
Section: Results and Discussion Chemistrymentioning
confidence: 99%
“…Khellin has been extensively used by the pharmaceutical industry as basic raw material for the development of drugs such as the anti-asthmatic agent sodium cromoglycate or the widely used anti-arrhythmic drug amiodarone [18]. Recent studies identified derivatives of khellin and visnagin as suitable agents to treat different types of tumors, epileptic seizures, kidney stones and inflammatory diseases [1922]. Due to its photosensitizing properties and lesser phototoxic side-effects compared to psoralens, khellin is also used in the photochemotherapy (khellin treatment plus ultraviolet A irradiation; KUVA) of vitiligo, a pigmentation disorder of the skin [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly used as a remedy for kidney stones by slowing the buildup of calcium oxalate and by acting as a diuretic [23,24]. Advanced studies identified derivatives of KH to treat different types of tumors, epileptic seizures and inflammatory diseases [25][26][27]. Moreover, a previous study performed on the aqueous extract of Ammi Visnaga proved its significant antidiabetic effect in both normal and diabetic rats [28].…”
Section: Introductionmentioning
confidence: 99%